Needs assessment of ophthalmology education for primary care physicians in training: comparison with the International Council of Ophthalmology recommendations - Chan, Toby YB (Dove Medical Press, 2011)
BACKGROUND: This cross-sectional survey assessed the adequacy of ophthalmology teaching in undergraduate medical education and evaluated the comfort level of family medicine residents in diagnosing and managing common ophthalmic conditions. METHODS: Postgraduate year 1 and 2 family medicine residents at the University of Western Ontario were recruited for this study. The main outcome measures were hours of classroom and clinic-based instruction on ophthalmology during undergraduate medical education, and the comfort level in ophthalmic clinical skills and managing various ophthalmic conditions. RESULTS: In total, 54 (33.3%) of 162 family medicine residents responded to the survey. Residents reported an average of 27.1 ± 35.1 hours and 39.8 ± 47.1 hours of classroom and clinical ophthalmology instruction, respectively. However, most residents (80%) responded as feeling only “somewhat comfortable” or “not at all comfortable” in assessing and managing common ophthalmic conditions, including ocular emergencies, such as acute angle closure glaucoma and ocular chemical burn. A positive correlation was seen between overall comfort level and hours of classroom instruction (P < 0.05). CONCLUSION: The number of hours of ophthalmology training received by family medicine residents during medical school meets the International Council of Ophthalmology Task Force recommendations. However, family medicine residents appear to be uncomfortable in handling treatable but potentially sight-threatening ocular conditions. Standardizing the undergraduate medical education ophthalmology curriculum and increasing hours of ophthalmology training during postgraduate family medicine residency may be useful in bridging this gap in knowledge.